Islamic government and religious authority in the political philosophy of Allameh Tabatabaei - mojtaba ghaderi; hossein ghasemi; mohammadsadegh nosratpanah (رهیافتهای سیاسی و بین المللی)
Using Skinner's intentional method, the present research considers the publication of the articles "Walayat and Za'amat in Islam" and "Ijtihad and Taqlid in Islam and Shia" by Allameh Tabatabai as his speech act in the 1340s, with the aim of formulating the theoretical plan of philosophy. Allameh Tabatabai's politics and understanding of his intention from the publication of these articles has been organized. This research, by answering the question "What is the plan of Islamic government and religious authority in the political philosophy of Allameh Tabatabai?", by examining the contextual (social-historical) and textual conditions (published articles), compares his plan with other thinkers of this period.In the end, it is clear that Allameh Tabatabaei formulates the relationship between the people and the organization of the province by rationally proving the necessity of the Islamic government and the guardianship of the jurist in the age of occultation. The findings of the research show that his intention with this action was "the rational and philosophical stabilization of the social and political system of religion, centered on the formation of the province organization".Using Skinner's intentional method, the present research considers the publication of the articles "Walayat and Za'amat in Islam" and "Ijtihad and Taqlid in Islam and Shia" by Allameh Tabatabai as his speech act in the 1340s, with the aim of formulating the theoretical plan of philosophy. Allameh Tabatabai's politics and understanding of his intention from the publication of these articles has been organized. This research, by answering the question "What is the plan of Islamic government and religious authority in the political philosophy of Allameh Tabatabai?", by examining the contextual (social-historical) and textual conditions (published articles), compares his plan with other thinkers of this period.In the end, it is clear that Allameh Tabatabaei formulates the relationship between the people and the organization of the province by rationally proving the necessity of the Islamic government and the guardianship of the jurist in the age of occultation. The findings of the research show that his intention with this action was "the rational and philosophical stabilization of the social and political system of religion, centered on the formation of the province organization".Using Skinner's intentional method, the present research considers the publication of the articles "Walayat and Za'amat in Islam" and "Ijtihad and Taqlid in Islam and Shia" by Allameh Tabatabai as his speech act in the 1340s, with the aim of formulating the theoretical plan of philosophy. Allameh Tabatabai's politics and understanding of his intention from the publication of these articles has been organized. This research, by answering the question "What is the plan of Islamic government and religious authority in the political philosophy of Allameh Tabatabai?", by examining the contextual (social-historical) and textual conditions (published articles), compares his plan with other thinkers of this period.In the end, it is clear that Allameh Tabatabaei formulates the relationship between the people and the organization of the province by rationally proving the necessity of the Islamic government and the guardianship of the jurist in the age of occultation. The findings of the research show that his intention with this action was "the rational and philosophical stabilization of the social and political system of religion, centered on the formation of the province organization".